Integration of AI and Wearable Devices for Continuous Cardiac Health Monitoring - Hira Zainab; Arbaz Haider Khan; Roman Khan; Hafiz Khawar Hussain (Information Technology and Science (ITScience), 2024)
The all-new integrative and wearable technology and AI universal steady cardiac health checkup will redefine the entire concept of cardiovascular treatment where checkup-detection-diagnosis of diseases will be done at early stage, followed by targeted therapy in real time. In as much as pertains the improvement of cardiac health results, this paper presents the prospects and threats associated with the integration of wearable devices such as heart rate monitor, ECG and other similar devices with AI algorithms. It also means that benchmarks that result from processing data from wearable’s can be established for AI systems in order to predict outcomes and consequently develop better care plans for ordinary patients. However, as of now, there are definite some certain ethically legally, and policy relevant concern with these technologies. Most is do with data ownership and privacy as well as understanding and obtaining the patients consent, dealing with the bias issue in regards to artificial intelligence basic decision making and ensuring explicit accountability and transparency throughout the process. Still to encourage innovation, and more mixing of smart wearable’s and artificial intelligence, it means that the requirements have to be adaptive to guarantee safety without necessarily denting the set effectiveness. Another shift that has to occur in reimbursement structures is that the various new technologies have to be made available for use and, therefore, appropriate reimbursement structures for them has to be promoted. In addition, the assessment equally applauds that for AI to complement rather than supplant human discretion, the balance of maintaining, on the one hand, the doctor-patient relationship and, on the other hand, the technical should be achieved. After comparing the major concepts of both the wearable technology and the artificial intelligence, the two would revolutionaries the monitoring of cardiac health. However, success in the outgoing needs such important aspects as access, ethical and legal question to monitor the position that the achieved success does not deepen health inequality.